If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -12 = 4(2x + -1) Reorder the terms: -12 + 4x = 4(2x + -1) Reorder the terms: -12 + 4x = 4(-1 + 2x) -12 + 4x = (-1 * 4 + 2x * 4) -12 + 4x = (-4 + 8x) Solving -12 + 4x = -4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -12 + 4x + -8x = -4 + 8x + -8x Combine like terms: 4x + -8x = -4x -12 + -4x = -4 + 8x + -8x Combine like terms: 8x + -8x = 0 -12 + -4x = -4 + 0 -12 + -4x = -4 Add '12' to each side of the equation. -12 + 12 + -4x = -4 + 12 Combine like terms: -12 + 12 = 0 0 + -4x = -4 + 12 -4x = -4 + 12 Combine like terms: -4 + 12 = 8 -4x = 8 Divide each side by '-4'. x = -2 Simplifying x = -2
| 9x-25=6x-34 | | -8x+29=61 | | y=-log(3)*(3x-6) | | v/3-4=1 | | 2.3+1.8a=5.1 | | 0x=-14 | | 2.1b+45.2=3.2-8.4b | | 8-t=10-7 | | z/11=11 | | 8-7=k/11 | | w+11=12 | | 12v+12v=1 | | a/3=6-1 | | -1y-2x=9 | | 100/45=14 | | 5m+24=29 | | 9+14=y | | 6x-280=180 | | 12x+14x+3y= | | -x-41=4(5x-5) | | 4(2x-3)-10=5x+5 | | X+6x-280=180 | | x/50=0.20 | | 2(x+6.2)+2.2=8.7x+7 | | -8.3=5(-1.4-b) | | 2x+y=264 | | 8(s-1)-6.1=2.9s+8 | | (2x-1)/3=1-x | | 14m+4n-5m+7n= | | (2x-1)/3=1_x | | z=4x^2+y^2-6x | | 2(x-3)=3(2x-10) |